Efektivitas Konseling Seksual Model PLISSIT terhadap Fungsi Seksual Perempuan dengan Kanker Payudara: Literatur Review - Dewi Damayanti; Shanty Chloranyta; Febri Adriati; Sinta WIjayanti; Fitri Yuliastuti; Sapti Ayubana; Yulia Indah Permata Sari (Universitas Malahayati Lampung, 2023)
ABSTRACT As one of the most common treatments for breast cancer, mastectomy has adverse effects on the quality of sexual life and sexual functioning in the impacted women. Various strategies have therefore been proposed to resolve their sexual problems. To identify the effectiveness of sexual counseling using the PLISSIT Model on the sexual function of women with breast cancer. The database used to identify suitable articles obtained from Scopus, PubMed, ProQuest, CINAHL, and Science Direct was limited from 2011-2019, English, and full text articles. The literature review used the keywords breast cancer, sexual function, sexual counseling model, sexual health models. 7 articles met the inclusion criteria. PLISSIT stands for four level of intervention, namely Permission, Limited Information, Specific Suggestions, and Intensive Care. This model is designed for sexual problems, including nursing care measures in the sexual dimension. The frequency of counseling sessions was conducted once a week, for five weeks, with a duration of approximately 90-120 minutes. The PLISSIT Model is effective in improving sexual function in women with breast cancer. Application of the PLISSIT model approach, namely Permission, Limited Information, Specific Suggestions, and Intensive Care to be used in dealing with sexual function problems in women with breast cancer Keywords: Breast Cancer, PLISSIT Model , Sexual Counseling Model, Sexual Function ABSTRAK Sebagai salah satu pengobatan kanker payudara yang paling umum, mastektomi memiliki dampak yang negatif pada kualitas kehidupan seksual dan fungsi seksual pada perempuan yang menjalaninya. Berbagai strategi telah diusulkan untuk menyelesaikan masalah seksual pada perempuan dengan kanker payudara. untuk mengidentifikasi efektivitas dari konseling seksual dengan menggunakan model PLISSIT terhadap fungsi seksual perempuan yang menderita kanker payudara. Database digunakan untuk mengidentifikasi artikel yang sesuai diperoleh dari Scopus, PubMed, ProQuest, CINAHL, dan Science Direct terbatas untuk tahun 2011 hingga 2019, bahasa Inggris dan teks lengkap. Tinjauan literatur menggunakan kata kunci fungsi seksual, kanker payudara, model konseling seksual, model kesehatan seksual. Dalam pencarian artikel menggunakan. 7 artikel memenuhi kriteria inkulusi. PLISSIT adalah singkatan dari empat tingkat intervensi yaitu Permission, Limited Information, Specific Suggestions, and Intensive Care. Model ini dirancang untuk masalah seksual, termasuk tindakan asuhan keperawatan dalam dimensi seksual. Frekuensi sesi konseling dilakukan seminggu sekali, selama lima minggu, dengan durasi kurang lebih 90-120 menit. Model PLISSIT efektif dalam meningkatkan fungsi seksual pada perempuan dengan kanker payudara. Penerapan pendekatan model PLISSIT yakni Permission, Limited Information, Specific Suggestions, and Intensive Care dalam digunakan dalam menangani masalah fungsi seksual pada perempuan dengan kanker payudara. Kata Kunci: Fungsi Seksual, Kanker Payudara, Model Konseling Seksual, Model PLISSIT